The effects of diatomite addition on the pore characteristics of a pyrophyllite support layer - Ha, Jang-Hoon; Lee, Jongman; Song, In-Hyuck; Lee, Sang-Hyup (Ceramics international, 2015)
Recently, porous ceramic membranes have become a subject of special interest due to their outstanding thermal and chemical stability. To alleviate the manufacturing cost issues of these porous ceramic membranes, recent research has been focused on the utilization of low cost natural materials. Therefore, in this paper, we report the results of our efforts to determine whether we could utilize diatomite as a pore former and whether we could prepare a pyrophyllite–diatomite composite support layer that could effectively control the largest pore size and permeability. The pore characteristics of the specimens were studied by scanning electron micrography, mercury porosimetry, and capillary flow porosimetry.